Menumbuhkan Minat Sains Sejak Dini: Kegiatan Pengenalan IPA di SDN 1 Tumbang Rungan: Cultivating Interest in Science from an Early Age: Science Introduction Activities at SDN 1 Tumbang Rungan - Suhartono, Suhartono; Sundari, Resti; Vari, Yonatan; Fauzi, Toni Dwi; Hartanto, Theo Jhoni; Dinata, Pri Ariadi Cahya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Introducing science to elementary school students in a fun way is a strategic step in establishing a foundation for scientific thinking from an early age. However, the reality in the field shows that the science learning approach is still conventional and less interactive. The limited use of experiments or engaging exploratory activities contributes to a lack of interest and enthusiasm for science among elementary school students. This diminished interest ultimately leads to a poor understanding of scientific concepts. To tackle this challenge, this community service initiative is centered around the theme